2002
DOI: 10.1002/jbm.10157
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of a bioactive scaffold for bone tissue engineering

Abstract: Revision cases of total hip implants are complicated by the significant amount of bone loss. New materials and/or approaches are needed to provide stability to the site, stimulate bone formation, and ultimately lead to fully functional bone tissue. Porous bioactive glasses (prepared from 45S5 granules, 45% SiO2, 24.5% Na2O, 24.5% CaO, and 6% P2O5) have been developed as scaffolds for bone tissue engineering and have been studied in vitro. In this study, we investigated the incorporation of tissue-engineered co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
0
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(119 citation statements)
references
References 41 publications
1
114
0
4
Order By: Relevance
“…However, some of these ceramics degrade very slowly, with crystalline HA being a very stable CaP in the biological environment (table 1) (Marcacci et al 2007;Chen et al 2008). More recently, bioactive silicate glasses and glass -ceramics have been investigated in their application as scaffolds (Livingston et al 2002;Di Nunzio et al 2004;Vitale-Brovarone et al 2004;Chen, Q. Z. et al 2006;Fu et al 2007;Vitale-Brovarone et al 2008).…”
Section: Inorganic Scaffoldsmentioning
confidence: 99%
“…However, some of these ceramics degrade very slowly, with crystalline HA being a very stable CaP in the biological environment (table 1) (Marcacci et al 2007;Chen et al 2008). More recently, bioactive silicate glasses and glass -ceramics have been investigated in their application as scaffolds (Livingston et al 2002;Di Nunzio et al 2004;Vitale-Brovarone et al 2004;Chen, Q. Z. et al 2006;Fu et al 2007;Vitale-Brovarone et al 2008).…”
Section: Inorganic Scaffoldsmentioning
confidence: 99%
“…Another study used a mesh on the tensile side of CPC to increase the work-to-fracture [45]. Macropores were built into implants to facilitate cell infiltration, tissue ingrowth, and implant fixation [3,6,17,18,20,24,[26][27][28]301. Our recent studies incorporated a variety of fibers, as well as water-soluble porogens, into CPC to obtain strength as well as macropores for bone ingrowth [46,49].…”
Section: H H K Xu C G Siinon Jr 1 J O U~~i N Imentioning
confidence: 99%
“…Indeed, numerous in vivo and in vitro studies have shown that 45S5 Bioglass ® can stimulate bone regeneration (Bosetti et al 2003;Gough et al 2004;Livingston et al 2002;Loty et al 2001;Tsigkou et al 2007;Xynos et al 2000). As a result, Bioglass ® is said to be both osteoproductive and osteoconductive.…”
Section: Introductionmentioning
confidence: 99%